Soft magnetic powder
By adjusting the specific heat treatment temperature parameters of soft magnetic powder, the problem of difficult temperature control in the preparation of nanocrystalline materials is solved, and the performance stability and magnetic properties of nanocrystalline materials are achieved.
Patent Information
- Application Number
- JP2022018935
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-02-09
AI Technical Summary
During the preparation of nanocrystalline materials, the heat treatment of soft magnetic powder leads to self-heating, making it difficult to control the temperature, resulting in unstable performance of nanocrystalline materials.
By adjusting the glass transition temperature Tg, the first crystallization start temperature Tx1 and the second crystallization start temperature Tx2 of the soft magnetic powder, it is ensured that ΔTx=Tx1-Tg≤50°C and ΔT=Tx2-Tx1 are between 65°C and 135°C, the self-heating phenomenon is suppressed, and nanocrystalization is carried out stably.
The temperature control of soft magnetic powder during nanocrystalization is realized, ensuring the stable performance of nanocrystalline materials, fully precipitate fine crystals, and improving magnetic properties.
Smart Images

Figure 0007662553000009 
Figure 0007662553000001 
Figure 0007662553000002
Abstract
Description
[Technical field]
[0001] The present invention relates to soft magnetic powders, and in particular to soft magnetic powders used in magnetic parts. [Background technology]
[0002] Magnetic cores that constitute magnetic components are required to have excellent magnetic properties (high saturation magnetic flux density and low core loss). Nanocrystalline materials are known as magnetic materials that can realize such magnetic properties. Nanocrystalline materials can be obtained by heat treating soft magnetic powder in a nanocrystallization process. Soft magnetic powders used to prepare nanocrystalline materials are disclosed in, for example, Patent Document 1 and Patent Document 2. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5632608 [Patent Document 2] Patent No. 6741108 Summary of the Invention [Problem to be solved by the invention]
[0004] The heat treatment in the nanocrystallization process causes the soft magnetic powder to self-heat. Therefore, it is difficult to control the temperature of the soft magnetic powder during the nanocrystallization process. As a result, the nanocrystalline material obtained by the nanocrystallization process has a problem that its characteristics are prone to variation. In other words, it is difficult to stably perform nanocrystallization of the soft magnetic powder.
[0005] Therefore, an object of the present invention is to provide a soft magnetic powder that can be stably nano-crystallized. [Means for solving the problem]
[0006] The present invention provides a first soft magnetic powder, which is a soft magnetic powder, The soft magnetic powder has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2, The first crystallization onset temperature Tx1 is 400° C. or higher and 475° C. or lower, The difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50° C. or less, The difference ΔT between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is ΔT=Tx2-Tx1, which is equal to or higher than 65° C. and equal to or lower than 135° C. A soft magnetic powder is provided.
[0007] The present invention also provides a second soft magnetic powder, which is the first soft magnetic powder, The first crystallization starting temperature Tx1 is 420° C. or higher and 460° C. or lower. A soft magnetic powder is provided.
[0008] The present invention also provides a third soft magnetic powder, which is the first or second soft magnetic powder, The difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 20° C. or more and 50° C. or less. A soft magnetic powder is provided.
[0009] Further, the present invention provides a fourth soft magnetic powder, which is any one of the first to third soft magnetic powders, The difference ΔT between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 (ΔT=Tx2−Tx1) is 75° C. or more. A soft magnetic powder is provided.
[0010] Further, the present invention provides a fifth soft magnetic powder, which is any one of the first to fourth soft magnetic powders, The soft magnetic powder is represented by the composition formula FeaSibPcBdCuxCryNbz, 75.4at%≦a≦80.4at% 0at%≦b≦9at% 4.5at%≦c≦12at% 4at%≦d≦12at% 0.3at%≦x≦0.9at% 0at%≦y+z≦5at% is A soft magnetic powder is provided.
[0011] The present invention also provides a sixth soft magnetic powder, which is the fifth soft magnetic powder, 77at%≦a≦79at% is A soft magnetic powder is provided.
[0012] The present invention also provides a seventh soft magnetic powder, which is the sixth soft magnetic powder, A part of the Fe, which is 3 at % or less of the entire composition, is replaced with one or more elements selected from Co, Ni, Zn, Zr, Hf, Mo, Ta, W, Ag, Au, Pd, K, Ca, Mg, Sn, Ti, V, Mn, Al, S, C, O, N, Bi and rare earth elements. A soft magnetic powder is provided.
[0013] The present invention also provides an eighth soft magnetic powder, which is any one of the first to seventh soft magnetic powders, The average particle size is 1 μm or more and 20 μm or less. A soft magnetic powder is provided.
[0014] Furthermore, the present invention provides a ninth soft magnetic powder, which is any one of the first to eighth soft magnetic powders, The crystallinity after quenching is 10% or less. A soft magnetic powder is provided. Effect of the Invention
[0015] Since the soft magnetic powder of the present invention has a glass transition temperature Tg, heat absorption occurs due to the glass transition in the nanocrystallization process, and self-heating during nanocrystallization is suppressed. In addition, the soft magnetic powder of the present invention has a first crystallization start temperature Tx1 and a second crystallization start temperature Tx2 that satisfy a predetermined temperature condition. Therefore, the soft magnetic powder of the present invention can stably perform nanocrystallization and sufficiently precipitate fine nanocrystals. [Brief description of the drawings]
[0016] [Figure 1] 1 is a graph showing the results of differential scanning calorimetry (DSC) of soft magnetic powder according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The soft magnetic powder according to one embodiment of the present invention is an Fe-based soft magnetic alloy powder having Fe as a main element and an amorphous phase as a main phase. The composition will be described later. The soft magnetic powder according to this embodiment is used, for example, in the manufacture of magnetic cores for magnetic components. In the process of manufacturing the magnetic cores, the soft magnetic powder is heat-treated to nano-crystallize it.
[0018] The soft magnetic powder according to the present embodiment can be produced by various manufacturing methods. For example, the soft magnetic powder may be produced by an atomization method such as a water atomization method or a gas atomization method. In the powder production process by the atomization method, first, raw materials are prepared. Next, the raw materials are weighed to have a predetermined composition (listed in Table 1-8) and melted to produce a molten alloy. Next, the molten alloy is discharged from a nozzle and broken into alloy droplets using high-pressure gas or water, thereby producing fine soft magnetic powder.
[0019] In the above powder production process, the gas used for the division may be an inert gas such as argon or nitrogen. In addition, in order to improve the cooling rate, the alloy droplets immediately after division may be rapidly cooled by contacting them with a cooling liquid or solid, or the alloy droplets may be further divided into smaller droplets. When a liquid is used for cooling, for example, water or oil may be used. When a solid is used for cooling, for example, a rotating copper roll or a rotating aluminum plate may be used. However, the liquid or solid for cooling is not limited to these, and various materials may be used.
[0020] In addition, in the above powder preparation process, the powder shape and particle size of the soft magnetic powder can be adjusted by changing the preparation conditions.
[0021] The soft magnetic powder according to this embodiment has the characteristics shown in Fig. 1. More specifically, the soft magnetic powder according to this embodiment has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. Here, the first crystallization onset temperature Tx1 is a temperature that depends on the bcc-Fe(-Si) precipitation reaction (first crystallization reaction), and the second crystallization temperature Tx2 is a temperature that depends on the compound precipitation reaction (second crystallization reaction).
[0022] In this embodiment, the first crystallization start temperature Tx1 is in a predetermined range. In addition, in this embodiment, the first crystallization start temperature Tx1 and the glass transition temperature Tg have a predetermined relationship. Furthermore, in this embodiment, the first crystallization start temperature Tx1 and the second crystallization temperature Tx2 have a predetermined relationship. By satisfying these requirements, when the soft magnetic powder of this embodiment is subjected to a heat treatment for nanocrystallization, self-heating is suppressed by the endothermic heat associated with the glass transition, and fine nanocrystals can be sufficiently precipitated. The soft magnetic powder of this embodiment will be described in detail below.
[0023] In this embodiment, the first crystallization start temperature Tx1 is 400°C or more and 475°C or less. This is because soft magnetic powders produced by the atomization method with Tx1<400°C have poor amorphous properties after quenching and do not provide good magnetic properties. In addition, soft magnetic powders with Tx1>475°C tend to increase the temperature of the surrounding atmosphere due to heat generated during nanocrystallization (heat treatment), which tends to cause crystal grains to become coarse, resulting in a deterioration of the soft magnetic properties.
[0024] In the present embodiment, the first crystallization onset temperature Tx1 is preferably 420° C. or more and 460° C. or less. A soft magnetic powder having a first crystallization onset temperature Tx1 in this range has good amorphousness after quenching, and also suppresses the temperature rise in the surrounding atmosphere due to heat generated during heat treatment, resulting in good soft magnetic properties after heat treatment.
[0025] In this embodiment, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50° C. or less. This is because a supercooled liquid region is necessary to utilize the endothermic reaction accompanying the glass transition during crystallization. In addition, if ΔTx is too large, the endothermic reaction and the nanocrystallization (exothermic) reaction are unlikely to occur simultaneously, which leads to coarsening of the crystals and deterioration of the magnetic properties.
[0026] The difference ΔTx is preferably 20° C. or more. If ΔTx is 20° C. or more, the amount of heat absorbed by the glass transition is sufficiently large, so that the temperature rise caused by the nanocrystallization (exothermic) reaction can be effectively suppressed, resulting in good soft magnetic properties.
[0027] Furthermore, in this embodiment, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is 65°C or more and 135°C or less. If ΔT is below 65°C, the temperature rise caused by the first crystallization reaction promotes the second crystallization (compound precipitation) reaction. Also, if ΔT exceeds 135°C, the soft magnetic powder has poor amorphousness and good soft magnetic properties cannot be obtained.
[0028] In the present embodiment, the difference ΔT is preferably 75° C. or more and 120° C. or less. This is because soft magnetic powder having a difference ΔT in this range can be heat-treated without causing a secondary crystallization (compound precipitation) reaction, and has good amorphous properties and good soft magnetic properties.
[0029] The soft magnetic powder according to the present embodiment has the composition formula Fe a S b P c B d Cu x Cr y Nb z Here, a, b, c, d, x, y, and z are values that satisfy the conditions of 75.4 at%≦a≦80.4 at%, 0 at%≦b≦9 at%, 4.5 at%≦c≦12 at%, 4 at%≦d≦12 at%, 0.3 at%≦x≦0.9 at%, 0 at%≦y+z≦5 at%.
[0030] In the soft magnetic powder according to the present embodiment, the Fe element is the main element and is an essential element responsible for magnetism. The higher the Fe ratio, the more the magnetic flux density Bs can be improved and the raw material price can be reduced. Furthermore, if the Fe ratio falls below 75.4 at%, Tx1 becomes high and ΔT becomes small. This makes it difficult to heat treat the soft magnetic powder, and the magnetic properties after heat treatment deteriorate. Furthermore, if the Fe ratio exceeds 80.4 at%, the amorphous nature decreases and the soft magnetic properties deteriorate.
[0031] In the present embodiment, the ratio of Fe element is preferably 77 at%≦a≦79 at%. This is because soft magnetic powders with a ratio of Fe element in this range have good amorphousness (crystallinity less than 3%), a wide ΔT (75°C or higher), and good soft magnetic properties after heat treatment.
[0032] In the soft magnetic powder according to the present embodiment, the Si element is an element responsible for forming the amorphous phase. When the Si element is contained in the soft magnetic powder, ΔT increases, and the heat treatment can be performed stably. However, when the ratio of Si exceeds 9 at%, the amorphous forming ability decreases, and it becomes impossible to obtain a soft magnetic powder having an amorphous phase as the main phase.
[0033] In the soft magnetic powder according to the present embodiment, the P element is an essential element responsible for the formation of an amorphous phase. The P element facilitates the formation of a fine and uniform nanocrystalline structure after heat treatment, so that good magnetic properties can be obtained. If the proportion of P is below 4.5 at%, the amorphous forming ability decreases. In addition, it becomes difficult to form a fine and uniform nanocrystalline structure after heat treatment, so that the soft magnetic properties decrease. On the other hand, if the proportion of P is high, Tx1 decreases. Also, if the proportion of P exceeds 12 at%, the balance with other metalloid elements becomes poor, and the amorphous forming ability decreases. Also, if the proportion of P exceeds 12 at%, the saturation magnetic flux density Bs decreases significantly.
[0034] In the soft magnetic powder according to the present embodiment, the B element is an essential element responsible for forming an amorphous phase. If the proportion of B is less than 4 at%, it becomes difficult to form an amorphous phase by quenching, and good magnetic properties cannot be obtained. Furthermore, if the proportion of B is high, Tx1 becomes high. If the proportion of B exceeds 12 at%, the melting point becomes high, which is not preferable in terms of production, and the ability to form an amorphous phase also decreases.
[0035] In the soft magnetic powder according to the present embodiment, the Cu element is an essential element that contributes to the formation of the nanocrystalline phase. If the proportion of Cu is below 0.3 at%, cluster precipitation during heat treatment is low, making uniform nanocrystallization difficult. If the proportion of Cu exceeds 0.9 at%, the amorphous forming ability decreases, making it difficult to obtain soft magnetic powder with high amorphous properties. In the soft magnetic powder according to the present embodiment, the proportion of the Cu element is preferably less than 0.7 at%. This is because soft magnetic powders within this range have good amorphous properties, enable uniform nanocrystallization, and have good soft magnetic properties after heat treatment.
[0036] In the soft magnetic powder according to the present embodiment, Cr and Nb are not essential. However, by adding Cr element, an oxide film is formed on the powder surface, improving corrosion resistance. In addition, by adding Nb element, there is an effect of suppressing bcc crystal grain growth during nanocrystallization, and it becomes easier to form a fine nanocrystalline structure. However, when Cr and Nb are added, the proportion of Fe is relatively decreased, and the saturation magnetic flux density Bs is decreased. In addition, the amorphous forming ability is also decreased. Therefore, it is preferable that the addition of Cr and Nb is 5 at% or less in total.
[0037] In the soft magnetic powder according to the present embodiment, a part of Fe may be replaced with one or more elements selected from Co, Ni, Zn, Zr, Hf, Mo, Ta, W, Ag, Au, Pd, K, Ca, Mg, Sn, Ti, V, Mn, Al, S, C, O, N, Bi and rare earth elements. By including such elements, uniform nano-crystallization after heat treatment becomes easy. However, in order to keep the adverse effects of these elements on magnetic properties and the like within an acceptable range, the ratio of these elements is preferably 3 at% or less of Fe.
[0038] In the soft magnetic powder according to the present embodiment, the average particle size is preferably 1 μm or more and 20 μm or less. Moreover, the crystallinity of the soft magnetic powder according to the present embodiment after quenching is preferably 10% or less. These values are for obtaining good magnetic properties after heat treatment.
[0039] Here, the quenching rate by the atomization method is 10 3 K / s or more. Preferably, 10 4 K / s or more. 3 If the melting point is less than K / s, the amount of precipitated initial crystals (mainly bcc-Fe) will be large, and the amount of amorphous phase will be small. Also, the composition of the amorphous phase in the soft magnetic powder will deviate from the desired composition, and the glass transition temperature Tg will not appear. Furthermore, the first crystallization onset temperature Tx1 will shift to the high temperature side, and the temperature peak due to the first crystallization will decrease.
[0040] Soft magnetic powders (hereinafter referred to as samples) were prepared as several examples and comparative examples, and the properties were evaluated, and the results are shown in Tables 1 to 8. The evaluations were performed as follows.
[0041] A thermal analysis was performed on each sample using a differential scanning calorimetry (DSC) analyzer. Specifically, the samples were subjected to thermal analysis from 40°C to 730°C at a heating rate of 10°C / min. This thermal analysis determined the glass transition temperature (Tg), the first crystallization onset temperature (Tx1: bcc-Fe(-Si) precipitation), and the second crystallization onset temperature (Tx2: Fe-B, Fe-P, etc. compound phase precipitation) of each sample.
[0042] Each sample was introduced into an electric furnace and heat-treated in an inert atmosphere. The heat treatment was performed by heating each sample to a specified temperature (listed in Table 1-8) and holding it for 30 minutes. The precipitated phase of each sample was evaluated by X-ray diffraction (XRD) before and after the heat treatment, and the proportion of the crystalline phase (degree of crystallinity) was calculated by the whole-powder-pattern decomposition method (WPPD method). Furthermore, the saturation magnetization of each sample was measured using a vibrating sample magnetometer (VSM), and the saturation magnetic flux density Bs of each sample was calculated from the measured saturation magnetization and the density of each sample. The density of each sample was determined using the Archimedes method. Furthermore, the particle size of the soft magnetic powder was evaluated using a laser particle size distribution meter, and the average particle size was calculated from the evaluated particle size.
[0043] Furthermore, dust cores were produced using each sample. The dust cores were produced by hot press molding or cold press molding, which will be described later. For each of the produced dust cores, the core loss Pcv was measured using a BH analyzer as an evaluation of the magnetic properties. The measurement conditions were determined based on the particle size of each sample and the production method of the dust core (listed in Table 1-8). Based on the measured core loss Pcv, the samples were classified into examples and comparative examples. In more detail, in each of Tables 1-6, samples with Pcv of 1250 kW / m 3 The following samples were used as examples. In addition, in each of Tables 7-8, 3 The following samples were used as examples.
[0044] The cold press molding was performed as follows. First, a binder was added to the soft magnetic powder sample so that the binder was 3% by weight, and the sample was stirred and mixed to obtain a granulated powder. Here, phenolic resin was used as the binder. Next, the particle size of the granulated powder was adjusted using a mesh with an opening of 500 μm to obtain a particle size-adjusted granulated powder. Next, a green compact was produced using the particle size-adjusted granulated powder. In detail, 2.0 g of the particle size-adjusted granulated powder was weighed, placed in a mold, and molded at a pressure of 490 MPa using a hydraulic automatic press. The green compact had a cylindrical shape with an outer diameter of 13 mm and an inner diameter of 8 mm. Next, the green compact was heated in an inert atmosphere using an infrared heating device. The heating was performed at a temperature increase rate of 300 ° C. per minute up to a specified heat treatment temperature (listed in Tables 1-5, 7-8), and the heat treatment temperature was maintained for 20 minutes. This heat treatment caused the binder to harden and the soft magnetic powder to nano-crystallize, and the green compact was transformed into a powder core. Thereafter, the powder magnetic core was air-cooled and removed from the mold.
[0045] The hot press molding was performed as follows. First, an insulating coating was formed on the surface of the soft magnetic powder sample to obtain an insulating coating powder. The insulating coating was formed by immersing the soft magnetic powder in a solution in which silicone resin was diluted with methanol, and then volatilizing the methanol. The amount of silicone resin coating (solid content) was 1% by weight relative to the soft magnetic powder. Next, a binder was added to the insulating coating powder so that the weight ratio was 1%, and the mixture was stirred and mixed to obtain a granulated powder. Next, the granulated powder was preformed to obtain a preformed body. In detail, 2.0 g of the granulated powder was weighed, placed in a mold, and preformed at a pressure of 150 MPa using a hydraulic automatic press. Next, the preformed body was subjected to main molding. In detail, a cylindrical mold with an outer diameter of 13 mm and an inner diameter of 8 mm, which had been heated in advance to a predetermined heat treatment temperature (listed in Table 6) by an electric heater, was used. With the lower punch loaded in the mold, the preformed body was filled in the mold, and the upper punch was loaded in the mold to apply a pressure of 1 GPa. The pressurized state was maintained for 30 seconds to transform the preform into a powder magnetic core, which was then removed from the die.
[0046] In addition to phenol resin and silicone resin, various organic and inorganic binders such as epoxy resin, polyamide resin, polyimide resin, melamine resin, polyurethane resin, water glass, etc. can be used as binders in cold press molding and hot press molding. The amount of binder may be appropriately determined in consideration of the powder particle size, applied frequency, application, etc.
[0047] (Examples 1-6 and Comparative Examples 1 and 2) As the raw materials of the soft magnetic powders of Examples 1-6 and Comparative Examples 1 and 2 shown in Table 1 below, industrial pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferrochrome and electrolytic copper were prepared. The raw materials were weighed so as to have the alloy compositions of Examples 1-6 and Comparative Examples 1 and 2 shown in Table 1, and melted by high-frequency melting in an argon atmosphere to prepare a molten alloy. Next, the prepared molten alloy was quenched by water atomization to prepare a soft magnetic powder with an average particle size of 8 to 14 μm. The prepared soft magnetic powder was subjected to thermal analysis by DSC and evaluation of the crystal phase by XRD. In addition, a powder core was prepared by cold press molding using the prepared soft magnetic powder, and magnetic properties were evaluated. Furthermore, the prepared soft magnetic powder was heat-treated in an electric furnace in an argon atmosphere at the heat treatment temperature shown in Table 1, and the heat-treated soft magnetic powder was subjected to saturation density Bs measurement by VSM. The results of measurement and evaluation of the prepared soft magnetic powder are shown in Table 1.
[0048] [Table 1]
[0049] Referring to Table 1, each of Examples 1-6 has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. In each of Examples 1-6, the first crystallization onset temperature Tx1 is in the range of 400°C or more and 475°C or less. In each of Examples 1-6, the difference ΔTx between the first crystallization onset temperature Tx1 and the glass transition temperature Tg, ΔTx=Tx1-Tg, is 50°C or less. In each of Examples 1-6, ΔTx is 20°C or more. In each of Examples 1-6, the difference ΔT between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1, ΔT=Tx2-Tx1, is in the range of 65°C or more and 135°C or less. In addition, in each of Examples 1-6, the crystallinity after quenching (as Q.) is 10% or less. In each of Examples 1 to 6, the average grain size is 8 to 14 μm, and the average grain size is within the range of 1 μm to 20 μm In addition, in each of Examples 1 to 6, the crystal phase is a bcc-Fe phase.
[0050] As shown in Table 1, each of Examples 1 to 6 satisfies the compositional requirements of the present invention. On the other hand, Comparative Example 1 has an Fe ratio of 81.4 at %, which does not satisfy the compositional requirements of the present invention. Also, Comparative Example 2 has an Fe ratio of 74.9 at %, which does not satisfy the compositional requirements of the present invention.
[0051] As shown in Table 1, the saturation magnetic flux density Bs of each of Examples 1 to 6 is 1.30 T or more, and the core loss Pcv is 1250 kW / m 3 In other words, each of Examples 1 to 6 has good magnetic properties.
[0052] In particular, the core loss Pcv of each of Examples 2 to 5 is 1000 kW / m as shown in Table 1. 3 In Examples 2-5, the first crystallization onset temperature Tx1 is in the range of 420° C. or more and 460° C. or less. Therefore, the first crystallization onset temperature Tx1 in the soft magnetic powder of the present invention is preferably in the range of 420° C. or more and 460° C. or less.
[0053] Furthermore, the core loss Pcv of each of Examples 3 and 4 is 750 kW / m as shown in Table 1. 3 In addition, the crystallinity of Examples 3-4 is 1.3% and 0.5%, respectively, and Examples 3-4 are excellent in amorphousness. In these Examples 3-4, the Fe ratio is in the range of 77 at% to 79 at%. Therefore, the Fe ratio in the soft magnetic powder of the present invention is preferably 77 at% or more and 79 at% or less.
[0054] On the other hand, Comparative Example 1 does not have a glass transition temperature Tg, as shown in Table 1. In Comparative Example 1, the crystallinity is 23.0%, which is much greater than 10%. In Comparative Example 2, the first crystallization onset temperature Tx1 is 480°C, which is greater than 475°C. In Comparative Example 2, the difference ΔTx between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 53°C, which is greater than 50°C. Furthermore, in Comparative Example 2, the crystal phase contains not only the bcc-Fe phase but also a compound phase (Com.).
[0055] As shown in Table 1, in Comparative Example 1, the saturation magnetic flux density Bs is 1.30 T or more, but the core loss Pcv is 1880 kW / m 3 and 1250kW / m 3 In Comparative Example 2, the saturation magnetic flux density Bs is 1.30 T or more, but the core loss Pcv is 1350 kW / m 3 and 1250kW / m 3 It exceeds.
[0056] (Examples 7-12 and Comparative Example 3) As the raw materials of the soft magnetic powders of Examples 7-12 and Comparative Example 3 shown in Table 2 below, industrial pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferrochrome and electrolytic copper were prepared. The raw materials were weighed so as to have the alloy compositions of Examples 7-12 and Comparative Example 3 shown in Table 2, and melted by high-frequency melting in an argon atmosphere to prepare a molten alloy. Next, the prepared molten alloy was quenched by water atomization to prepare a soft magnetic powder having an average particle size of 8 to 14 μm. The prepared soft magnetic powder was subjected to thermal analysis by DSC and evaluation of the crystal phase by XRD. In addition, a powder core was prepared by cold press molding using the prepared soft magnetic powder, and magnetic properties were evaluated. Furthermore, the prepared soft magnetic powder was heat-treated in an electric furnace in an argon atmosphere at the heat treatment temperature shown in Table 2, and the heat-treated soft magnetic powder was subjected to saturation density Bs measurement by VSM. The results of measurement and evaluation of the prepared soft magnetic powder are shown in Table 2.
[0057] [Table 2]
[0058] Referring to Table 2, each of Examples 7-12 has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. In each of Examples 7-12, the first crystallization onset temperature Tx1 is in the range of 400°C or more and 475°C or less. In each of Examples 7-12, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50°C or less. In each of Examples 7-12, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is in the range of 65°C or more and 135°C or less. In addition, in each of Examples 7-12, the crystallinity after quenching (as Q.) is 10% or less. In each of Examples 7 to 12, the average grain size is 8 to 14 μm, in the range of 1 μm or more and 20 μm or less, and in each of Examples 7 to 12, the crystal phase is a bcc-Fe phase.
[0059] As shown in Table 2, each of Examples 7 to 12 satisfies the compositional requirements of the present invention. On the other hand, Comparative Example 3 has a Si ratio of 9.5 at%, which does not satisfy the compositional requirements of the present invention (0 at%≦b≦9 at%).
[0060] As shown in Table 2, the saturation magnetic flux density Bs of each of Examples 7 to 12 is 1.30 T or more, and the core loss Pcv is 1250 kW / m 3 In other words, each of Examples 7-12 has good magnetic properties.
[0061] In particular, the core loss Pcv of Examples 8-11 is 1000 kW / m as shown in Table 2. 3 In these Examples 8 to 11, ΔT is 75° C. or more and 120° C. or less. Therefore, ΔT in the soft magnetic powder of the present invention is preferably 75° C. or more and 120° C. or less.
[0062] On the other hand, Comparative Example 3 does not have a glass transition temperature Tg, as shown in Table 2. In Comparative Example 3, the difference ΔT between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1, ΔT=Tx2-Tx1, is 140° C., exceeding 135° C. Furthermore, in Comparative Example 3, the crystallinity is 15.6%, exceeding 15%.
[0063] As shown in Table 2, in Comparative Example 3, the saturation magnetic flux density Bs was 1.30 T or more, but the core loss Pcv was 1500 kW / m 3 and 1250kW / m 3 This far exceeds the previous figure.
[0064] (Examples 13-17 and Comparative Examples 4 and 5) As the raw materials of the soft magnetic powders of Examples 13-17 and Comparative Examples 4 and 5 shown in Table 3 below, industrial pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferrochrome and electrolytic copper were prepared. The raw materials were weighed so as to obtain the alloy compositions of Examples 13-17 and Comparative Examples 4 and 5 shown in Table 3, and melted by high-frequency melting in an argon atmosphere to prepare a molten alloy. Next, the prepared molten alloy was gas atomized and then quenched with cooling water to prepare a soft magnetic powder having an average particle size of 8 to 14 μm. The prepared soft magnetic powder was subjected to thermal analysis by DSC and evaluation of the crystal phase by XRD. In addition, a powder core was prepared by cold press molding using the prepared soft magnetic powder, and magnetic properties were evaluated. Furthermore, the prepared soft magnetic powder was heat-treated in an electric furnace in an argon atmosphere at the heat treatment temperature shown in Table 3, and the heat-treated soft magnetic powder was subjected to saturation density Bs measurement by VSM. The measurement and evaluation results of the prepared soft magnetic powder are shown in Table 3.
[0065] [Table 3]
[0066] Referring to Table 3, each of Examples 13-17 has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. In each of Examples 13-17, the first crystallization onset temperature Tx1 is in the range of 400°C or more and 475°C or less. In each of Examples 13-17, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50°C or less. Furthermore, in each of Examples 13-17, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is in the range of 65°C or more and 135°C or less. In addition, in each of Examples 13-17, the crystallinity after quenching (as Q.) is 10% or less. In each of Examples 13 to 17, the average grain size is 8 to 14 μm, in the range of 1 μm to 20 μm, and the crystal phase is a bcc-Fe phase.
[0067] As shown in Table 3, each of Examples 13 to 17 satisfies the compositional requirements of the present invention. On the other hand, Comparative Example 4 has a P ratio of 4 at%, which does not satisfy the compositional requirements of the present invention (4.5 at%≦c≦12 at%). Comparative Example 5 has a P ratio of 12.5 at%, which does not satisfy the compositional requirements of the present invention (4.5 at%≦c≦12 at%).
[0068] As shown in Table 3, the saturation magnetic flux density Bs of each of Examples 13 to 17 was 1.30 T or more, and the core loss Pcv was 1250 kW / m 3 In other words, each of Examples 13-17 has good magnetic properties.
[0069] On the other hand, Comparative Example 4 does not have a glass transition temperature Tg, as shown in Table 3. In Comparative Example 5, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is 60°C, which is below 65°C. In Comparative Example 5, the crystallinity after quenching (as Q.) is 12.1%, which is more than 10%. Furthermore, in Comparative Example 5, the crystal phase contains not only the bcc-Fe phase but also a compound phase (Com.).
[0070] As shown in Table 3, in Comparative Example 4, the saturation magnetic flux density Bs was 1.30 T or more, but the core loss Pcv was 1430 kW / m 3 and 1250kW / m 3 In Comparative Example 5, the saturation magnetic flux density Bs is 1.30 T or more, but the core loss Pcv is 1550 kW / m 3 and 1250kW / m 3 This far exceeds the previous figure.
[0071] (Examples 3, 18-21 and Comparative Examples 6 and 7) As the raw materials of the soft magnetic powders of Examples 3, 18-21 and Comparative Examples 6 and 7 shown in Table 4 below, industrial pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferrochrome and electrolytic copper were prepared. The raw materials were weighed so as to have the alloy compositions of Examples 3, 18-21 and Comparative Examples 6 and 7 shown in Table 4, and melted by high-frequency melting in an argon atmosphere to prepare a molten alloy. Next, the prepared molten alloy was quenched by water atomization to prepare a soft magnetic powder with an average particle size of 8 to 14 μm. The prepared soft magnetic powder was subjected to thermal analysis by DSC and evaluation of the crystal phase by XRD. In addition, a powder core was prepared by cold press molding using the prepared soft magnetic powder, and magnetic properties were evaluated. Furthermore, the prepared soft magnetic powder was heat-treated in an electric furnace in an argon atmosphere at the heat treatment temperature shown in Table 4, and the heat-treated soft magnetic powder was subjected to saturation density Bs measurement by VSM. The results of measurement and evaluation of the prepared soft magnetic powder are shown in Table 4.
[0072] [Table 4]
[0073] Referring to Table 4, each of Example 3 and Examples 18-21 has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. In each of Example 3 and Examples 18-21, the first crystallization onset temperature Tx1 is in the range of 400°C or more and 475°C or less. In each of Example 3 and Examples 18-21, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50°C or less. Furthermore, in each of Example 3 and Examples 18-21, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is in the range of 65°C or more and 135°C or less. In addition, in each of Example 3 and Examples 18-21, the crystallinity after quenching (as Q.) is 10% or less. In each of Example 3 and Examples 18-21, the average grain size is 8 to 14 μm, in the range of 1 μm to 20 μm, and the crystal phase is a bcc-Fe phase in each of Example 3 and Examples 18-21.
[0074] As shown in Table 4, in addition to Example 3, each of Examples 18-21 satisfies the composition requirement of the present invention. On the other hand, Comparative Example 6 has a B ratio of 3.5 at%, which does not satisfy the composition requirement of the present invention (4 at%≦d≦12 at%). Moreover, Comparative Example 7 has a B ratio of 12.5 at%, which does not satisfy the composition requirement of the present invention (4 at%≦d≦12 at%).
[0075] As shown in Table 4, the saturation magnetic flux density Bs of each of Example 3 and Examples 18 to 21 is 1.30 T or more, and the core loss Pcv is 1250 kW / m 3 In other words, each of Example 3 and Examples 18 to 21 has good magnetic properties.
[0076] On the other hand, neither Comparative Example 6 nor Comparative Example 7 has a glass transition temperature Tg, as shown in Table 4. Furthermore, in Comparative Example 6 and Comparative Example 7, the crystallinity is 11.5% and 13.8%, respectively, which is greater than 10%.
[0077] As shown in Table 4, in Comparative Example 6, the saturation magnetic flux density Bs was 1.30 T or more, but the core loss Pcv was 1260 kW / m 3 and 1250kW / m 3 Similarly, in Comparative Example 7, the saturation magnetic flux density Bs is 1.30 T or more, but the core loss Pcv is 1390 kW / m 3 and 1250kW / m 3 It exceeds.
[0078] (Examples 19, 22-27 and Comparative Examples 8 and 9) As the raw materials of the soft magnetic powders of Examples 19, 22-27 and Comparative Examples 8 and 9 shown in Table 5 below, industrial pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferrochrome and electrolytic copper were prepared. The raw materials were weighed so as to have the alloy compositions of Examples 19, 22-27 and Comparative Examples 8 and 9 shown in Table 5, and melted by high-frequency melting in an argon atmosphere to prepare a molten alloy. Next, the prepared molten alloy was quenched by water atomization to prepare a soft magnetic powder with an average particle size of 8 to 14 μm. The prepared soft magnetic powder was subjected to thermal analysis by DSC and evaluation of the crystal phase by XRD. In addition, a powder core was prepared by cold press molding using the prepared soft magnetic powder, and magnetic properties were evaluated. Furthermore, the prepared soft magnetic powder was heat-treated in an electric furnace in an argon atmosphere at the heat treatment temperature shown in Table 5, and the heat-treated soft magnetic powder was subjected to saturation density Bs measurement by VSM. The results of measurement and evaluation of the prepared soft magnetic powder are shown in Table 5.
[0079] [Table 5]
[0080] Referring to Table 5, each of Example 19 and Examples 22-27 has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. In each of Example 19 and Examples 22-27, the first crystallization onset temperature Tx1 is in the range of 400°C or more and 475°C or less. In each of Example 19 and Examples 22-27, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50°C or less. Furthermore, in each of Example 19 and Examples 22-27, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is in the range of 65°C or more and 135°C or less. In addition, in each of Example 19 and Examples 22-27, the crystallinity after quenching (as Q.) is 10% or less. In each of Example 19 and Examples 22-27, the average grain size is 8 to 14 μm, in the range of 1 μm or more and 20 μm or less, and in each of Example 19 and Examples 22-27, the crystal phase is a bcc-Fe phase.
[0081] As shown in Table 5, in addition to Example 19, each of Examples 22-27 satisfies the composition requirement of the present invention. On the other hand, Comparative Example 8 has a Cu ratio of 1.0 at%, which does not satisfy the composition requirement of the present invention (0.3 at%≦x≦0.9 at%). Moreover, Comparative Example 9 has a Cu ratio of 0.2 at%, which does not satisfy the composition requirement of the present invention (0.3 at%≦x≦0.9 at%).
[0082] As shown in Table 5, the saturation magnetic flux density Bs of each of Examples 19 and 22-27 is 1.30 T or more, and the core loss Pcv is 1250 kW / m 3 In other words, each of Example 19 and Examples 22-27 has good magnetic properties.
[0083] In particular, the core loss Pcv of Examples 19 and 24-27 is 1000 kW / m 3 In these Examples 19 and 24 to 27, the Cu ratio is less than 0.7 at %. Therefore, the Cu ratio in the soft magnetic powder of the present invention is preferably 0.3 at % or more and less than 0.7 at %.
[0084] On the other hand, Comparative Example 8 does not have a glass transition temperature Tg, as shown in Table 5. In Comparative Example 8, the crystallinity is 13.5%, which is greater than 10%. In Comparative Example 9, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 62° C., which is less than 65° C. In Comparative Example 9, the crystal phase includes not only the bcc-Fe phase but also a compound phase (Com.).
[0085] As shown in Table 5, in Comparative Example 8, the saturation magnetic flux density Bs was 1.30 T or more, but the core loss Pcv was 1470 kW / m 3 and 1250kW / m 3 Similarly, in Comparative Example 9, the saturation magnetic flux density Bs is 1.30 T or more, but the core loss Pcv is 1520 kW / m 3 and 1250kW / m3 It exceeds.
[0086] (Examples 19, 28-31 and Comparative Example 10) As the raw materials of the soft magnetic powders of Examples 28-31 and Comparative Example 10 shown in Table 6 below, industrial pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferrochrome, niobium, and electrolytic copper were prepared. The raw materials were weighed so as to have the alloy compositions of Examples 28-31 and Comparative Example 10 shown in Table 6, and melted by high-frequency melting in an argon atmosphere to prepare a molten alloy. Next, the prepared molten alloy was quenched by high-pressure water atomization to prepare a soft magnetic powder with an average particle size of 3 to 8 μm. The prepared soft magnetic powder was subjected to thermal analysis by DSC and evaluation of the crystal phase by XRD. In addition, a dust core was prepared by hot press molding using the prepared soft magnetic powder, and magnetic properties were evaluated. Furthermore, the prepared soft magnetic powder was heat-treated in an argon atmosphere at the heat treatment temperature shown in Table 6, and the heat-treated soft magnetic powder was subjected to saturation density Bs measurement by VSM. The results of measurement and evaluation of the prepared soft magnetic powder are shown in Table 6.
[0087] [Table 6]
[0088] Referring to Table 6, each of Example 19 and Examples 28-31 has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. In each of Example 19 and Examples 28-31, the first crystallization onset temperature Tx1 is in the range of 400°C or more and 475°C or less. In each of Example 19 and Examples 28-31, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50°C or less. Furthermore, in each of Example 19 and Examples 28-31, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is in the range of 65°C or more and 135°C or less. In addition, in each of Example 19 and Examples 28-31, the crystallinity after quenching (as Q.) is 10% or less. In each of Example 19 and Examples 28 to 31, the average grain size is 3 to 8 μm, in the range of 1 μm to 20 μm, and the crystal phase is a bcc-Fe phase.
[0089] As shown in Table 6, in addition to Example 19, each of Examples 28 to 31 satisfies the composition requirements of the present invention. On the other hand, in Comparative Example 10, the sum of the Cr ratio and the Nb ratio is 5.5 at%, which does not satisfy the composition requirements of the present invention (0 at%≦y+z≦5 at%).
[0090] As shown in Table 6, the saturation magnetic flux density Bs of each of Examples 19 and 28 to 31 is 1.30 T or more, and the core loss Pcv is 1250 kW / m 3 In other words, each of Example 19 and Examples 28 to 31 has good magnetic properties.
[0091] On the other hand, in Comparative Example 10, as shown in Table 6, the saturation magnetic flux density Bs is 1.25 T, which is less than 1.30 T, and the core loss Pcv is 1300 kW / m 3 and 1250kW / m 3 It exceeds.
[0092] (Examples 32-42) As the raw materials of the soft magnetic powder of Examples 32-42 listed in Table 7 below, industrial pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferrochrome, electrolytic copper, ferrocarbon, CO, zinc, Sn, Ni, Mn, Al, and Ti were prepared. The raw materials were weighed so as to obtain the alloy composition of Examples 32-42 listed in Table 7, and melted by high-frequency melting in an argon atmosphere to prepare a molten alloy. Next, the prepared molten alloy was gas atomized and then quenched with cooling water to prepare a soft magnetic powder with an average particle size of 14 to 20 μm. The prepared soft magnetic powder was subjected to thermal analysis by DSC and evaluation of the crystal phase by XRD. In addition, a powder core was prepared by cold press molding using the prepared soft magnetic powder, and magnetic properties were evaluated. Furthermore, the prepared soft magnetic powder was heat treated in an electric furnace in an argon atmosphere at the heat treatment temperature shown in Table 7, and the heat-treated soft magnetic powder was subjected to saturation density Bs measurement by VSM. Table 7 shows the results of measurement and evaluation of the produced soft magnetic powder.
[0093] [Table 7]
[0094] Referring to Table 7, each of Examples 32-42 has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. In each of Examples 32-42, the first crystallization onset temperature Tx1 is in the range of 400°C or more and 475°C or less. In each of Examples 32-42, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50°C or less. In each of Examples 32-42, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is in the range of 65°C or more and 135°C or less. In addition, in each of Examples 32-42, the crystallinity after quenching (as Q.) is 10% or less. In each of Examples 32-42, the average grain size is 14 to 20 μm, in the range of 1 μm or more and 20 μm or less, and in each of Examples 32-42, the crystal phase is a bcc-Fe phase.
[0095] As shown in Table 7, in each of Examples 32-42, a portion (3 at % or less) of Fe is substituted with a predetermined element. More specifically, each of Examples 32 and 33 contains C. Example 34 contains Co. Example 35 contains Zn. Each of Examples 36 and 37 contains Sn. Example 38 contains Ni. Example 39 contains Mn. Example 40 contains Al. Example 41 contains Ti. Example 42 contains O.
[0096] As shown in Table 7, in each of Examples 32 to 42, the saturation magnetic flux density Bs was 1.30 T or more, and the core loss Pcv was 300 kW / m 3 In other words, each of Examples 32-42 has good magnetic properties. Note that the measurement conditions for the core loss Pcv in Table 7 are different from the measurement conditions for the core loss Pcv in Tables 1-6.
[0097] (Example 43) As the raw materials of the soft magnetic powder of Example 43 shown in Table 8 below, industrial pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferrochrome and electrolytic copper were prepared. The raw materials were weighed to obtain the alloy composition of Example 43 shown in Table 8, and melted by high-frequency melting in an argon atmosphere to prepare a molten alloy. Next, the prepared molten alloy was quenched by gas atomization to prepare a soft magnetic powder with an average particle size of 14 to 20 μm. The prepared soft magnetic powder was subjected to thermal analysis by DSC and evaluation of the crystal phase by XRD. In addition, a powder core was prepared by cold press molding using the prepared soft magnetic powder, and magnetic properties were evaluated. Furthermore, the prepared soft magnetic powder was heat-treated in an electric furnace in an argon atmosphere at the heat treatment temperature shown in Table 8, and the heat-treated soft magnetic powder was subjected to saturation density Bs measurement by VSM. The results of measurement and evaluation of the prepared soft magnetic powder are shown in Table 8.
[0098] [Table 8]
[0099] Referring to Table 8, Example 43 has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization temperature Tx2. In Example 43, the first crystallization onset temperature Tx1 is in the range of 400°C or more and 475°C or less. In Example 43, the difference ΔTx=Tx1-Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50°C or less. In Example 43, the difference ΔT=Tx2-Tx1 between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 is in the range of 65°C or more and 135°C or less. In addition, in Example 43, the crystallinity after quenching (as Q.) is 10% or less. In Example 43, the average particle size is 14 to 20 μm, and is in the range of 1 μm or more and 20 μm or less.
[0100] As shown in Table 8, the first crystallization onset temperature Tx1 of Example 43 is 442°C. This Example 43 was subjected to heat treatment at various temperatures from 400°C to 500°C. Regardless of the treatment temperature, a saturation magnetic flux density Bs of 1.30 T or more and a saturation magnetic flux density (M) of 300 kW / m 3 The following core loss Pcv was obtained. This shows that the soft magnetic powder of the present invention can obtain good magnetic properties even if the heat treatment is performed at a temperature lower or higher than the first crystallization onset temperature Tx1. However, referring to Table 7 in addition to Table 8, when the heat treatment temperature is close to the first crystallization onset temperature Tx1, the core loss Pcv is 200 kW / m 3 Therefore, it is preferable that the heat treatment temperature is close to the first crystallization onset temperature Tx1.
[0101] As described above, the powder magnetic core of Example 1-43 has excellent magnetic properties. From this, it can be said that the soft magnetic powder of Example 1-43 can stably perform nanocrystallization and can sufficiently precipitate fine nanocrystals.
[0102] Although the present invention has been described above with reference to several embodiments, the present invention is not limited to the above-described embodiments, and various modifications and changes are possible without departing from the spirit and scope of the present invention.
[0103] For example, the soft magnetic powder of the present invention may be one in which initial crystals are precipitated. In this case, low-grade, inexpensive materials can be used as raw materials. In addition, the amount of heat generated during heating can be suppressed. Furthermore, a high saturation magnetic flux density Bs can be expected.
[0104] In the above embodiment, the soft magnetic powder is manufactured by atomization, but other methods may be used. For example, a ribbon may be made from the molten alloy, and the ribbon may be pulverized to obtain the soft magnetic powder. In this case, a high saturation magnetic flux density Bs and a high magnetic permeability μ can be expected.
[0105] Furthermore, the soft magnetic powder of the present invention may have its surface coated with glass etc. This is expected to improve the electrical resistance and the flowability during the production of a magnetic core.
Claims
1. A soft magnetic powder comprising: The soft magnetic powder has a glass transition temperature Tg, a first crystallization onset temperature Tx1, and a second crystallization onset temperature Tx2, The first crystallization starting temperature Tx1 is 400° C. or higher and 475° C. or lower, The difference ΔTx = Tx1 - Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 50 ° C. or less, a difference ΔT between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 (T=Tx2−Tx1) is 65° C. or more and 135° C. or less; The soft magnetic powder is represented by the composition formula FeaSibPcBdCuxCryNbz, 75.4at%≦a≦80.4at% 0at%≦b≦9at% 4.5at%≦c≦12at% 4at%≦d≦12at% 0.3at%≦x≦0.9at% 0at%≦y+z≦5at% is Soft magnetic powder.
2. The soft magnetic powder according to claim 1, The first crystallization starting temperature Tx1 is 420° C. or higher and 460° C. or lower. Soft magnetic powder.
3. The soft magnetic powder according to claim 1 or 2, The difference ΔTx=Tx1−Tg between the first crystallization onset temperature Tx1 and the glass transition temperature Tg is 20° C. or more and 50° C. or less. Soft magnetic powder.
4. A soft magnetic powder according to any one of claims 1 to 3, The difference ΔT between the second crystallization onset temperature Tx2 and the first crystallization onset temperature Tx1 (ΔT=Tx2−Tx1) is 75° C. or more. Soft magnetic powder.
5. The soft magnetic powder according to any one of claims 1 to 4, 77at%≦a≦79at% is Soft magnetic powder.
6. The soft magnetic powder according to claim 5, A part of the Fe, which is 3 at % or less of the entire composition, is replaced with one or more elements selected from Co, Ni, Zn, Zr, Hf, Mo, Ta, W, Ag, Au, Pd, K, Ca, Mg, Sn, Ti, V, Mn, Al, S, C, O, N, Bi and rare earth elements. Soft magnetic powder.
7. A soft magnetic powder according to any one of claims 1 to 6, The average particle size is 1 μm or more and 20 μm or less. Soft magnetic powder.
8. A soft magnetic powder according to any one of claims 1 to 7, The crystallinity after quenching is 10% or less. Soft magnetic powder.
Citation Information
Patent Citations
Method of forming conductive film
JP1981032608A
Soft magnetic alloys and magnetic components
JP6741108B1
Titanium group powder metallurgy
US20050084407A1
Aluminum based metallic glass powder for efficient degradation of AZO dye and other toxic organic chemicals
US20170209853A1
Fe-BASED ALLOY COMPOSITION, SOFT MAGNETIC POWDER, MOLDED MEMBER, DUST CORE, ELECTRIC / ELECTRONIC COMPONENT, ELECTRIC / ELECTRONIC DEVICE, MAGNETIC SHEET, COMMUNICATIONS COMPONENT, COMMUNICATIONS DEVICE, AND ELECTROMAGNETIC INTERFERENCE-SUPPRESSING MEMBER
WO2016152269A1